Exploration of efficiency of nano calcium oxide (CaO) as catalyst for enhancement of biodiesel production - Muhammad Nor Fazli, Abd Malek; Livitra, Pushparaja; Noraini, Mat Hussin; Nurul Hajar, Embong; Bhuyar, Prakash; Mohd Hasbi, Ab. Rahim; Maniam, Gaanty Pragas (Slovak University of Agriculture, 2021)
Present work proposes on the synthesis of nano calcium oxide derived from waste cockle shell (Anadara granosa) and applied as heterogenous catalyst in biodiesel production via transesterification reaction under reaction parameter 15:1 methanol to oil ratio, 5 wt.% catalyst and 3 hour reation time and constant temperature at 65 ± 2 °C. The waste cockle shell was prepared in nano size via ball mill technique which was run for 36 hours at 350 rpm speed and then calcined at 900 °C for 2 hours to decompose calcium carbonate, CaCOî into nano calcium oxide, n-CaO. The catalyst was characterized by particle size analyzer, Transmission Electron Microscopy, Field Emission Scanning Electron Microscope, Surface Area Analyser, X-Ray Diffractometer, Fourier transform infrared, Hammet indicator and benzoic acid titration. Particle size of n-CaO catalyst was found within the range of 29 nm to 67.5 nm. Specific surface area of synthesised n-CaO is 8.41 m2/g with basicity strength of 0.055 mmol/g. Methyl ester conversion of palm oil with n-CaO as a catalyst was 88.87 wt.%.